Building a Foundation for Global Competence: Improving English Language Instruction in Indonesian Curriculum - Setiawati, Yulis (Institut Agama ISlam Negeri Palangka Raya, 2023)
The study intends to examine (1) curriculum planning for English study programs, (2) the English language curriculum's structure, (3) how the English language curriculum is put into practice to raise the caliber of graduates, and (4) other related topics. (5) To determine the encouraging and discouraging variables. To evaluate the English learning curriculum. The research technique uses qualitative methods to characterize study site activities, gather data through interviews, observations, and documentation, and evaluate planning and implementation to improve English study program graduates' achievement. research output (1) Students can work out issues with learning English (2) can produce findings regarding the topic of learning English (3) To study English, students can plan, manage, analyze, and apply themselves (4) The ability to speak and understand English is essential for the growth of the curriculum in Indonesia since it opens doors to worldwide communication and boosts one's ability to compete. This article emphasizes the significance of English in Indonesian curriculum and offers tips for successful integration. It aims to develop a curriculum that promotes linguistic proficiency, cultural sensitivity, and global competence by assessing advantages and difficulties.